Domestic energy use database for integrated energy planning - Afrane-Okese, Yaw (Department of Electrical Engineering, 2016)
One of the legacies of the apartheid policies in South Africa has been·the huge gap between rich and poor households in terms of their access to basic energy services. This study explores the essence of shifting from· supply-driven approach to an integrated framework in energy planning order to evolve policies that match national goals and objectives with the energy needs of the low-income households. The principles of Integrated Energy Planning (IEP) are outline for the household sector and the development of an energy database is identified as one of the important processes required in IEP. The design of the database is practically demonstrated by capturing existing secondary and primary data on energy use in low-income households in South Africa. The user-interface and on-line data analysis of the database are also illustrated. Furthermore, the data has been extensively analysed to show the factors that influence energy demand in the low-income households and how these factors may interact with one another. In·addition, energy grid-use data·has been aggregated from the· database as input into an energy modelling computer programme for estimating energy demand projections for low-income households. These energy demand projections are based on 'energy scenarios which investigate alternate energy supply options. Thus the study illustrates how energy use data can be organised into a tool for informing policy formulation. Bibliography: p. 154-156.